Structural and functional brain correlates of theory of mind impairment post-stroke. (December 2019) - Domínguez D, Juan F.; Nott, Zoie; Horne, Kristina; Prangley, Tarran; Adams, Alexandra G.; Henry, Julie D.; Molenberghs, Pascal
Abstract: The ability to understand the mental states of others – also known as Theory of Mind (ToM) – is critical for normal social interactions. We combine behavioural probes with structural and functional brain imaging to provide the first comprehensive analysis of ToM deficits following stroke using the Reading the Mind in the Eyes Test (RMET). First, fMRI was used to identify the functional brain network involved in a non-clinical cohort. Results indicated that, relative to a control task, the RMET increased activity in a widespread functional bilateral network comprising frontal and temporo-parietal areas. To investigate how damage to grey and white matter components of this network can lead to ToM impairment, parcel-based lesion-symptom mapping (PLSM), white-matter tract-wise statistical analysis (TSA) and disconnectome symptom mapping (DSM) were performed using structural images from 64 stroke patients. PLSM results revealed that low scores on the RMET were associated with damage centered around the right posterior frontal gyrus and insula. TSA and DSM results further revealed that low RMET scores were associated with damage to white-matter tracts connecting frontal and temporo-parietal components of the RMET functional network. Together, these findings suggest that making judgements about the mental states of others imposes demands on a large functional network that can easily be disrupted, both by damage to grey matter areas that form part of the network directly, or the white-matter pathways that connect them.